COMPARATIVE ANALYSIS OF PERFORMANCE CHARACTERISTICS OF JET VORTEX TYPE SUPERCHAGES - Rogovyi, A.; Voronova, Ye.; Роговой, А. С.; Воронова, Е. М.; Роговий, А. С.; Воронова, Є. М. (Харьковский национальный автомобильно-дорожный университет, 2016)
On the basis of mathematical modeling there was carried out a comparative analysis of characteristics of jet vortex type superchargers. Dependences of the energy performance of vortex ejector on the geometry parameters and the largest values in terms of efficiency as well as the coefficient of ejection are analyzed. There were built combined characteristics of vortex chamber pumps and vortex ejectors. Vortex chamber pump has advantage pressure in an exit channel over the vortex ejector, consequently there is a more effective power transmission from a working medium, besides the withdrawal of pumping medium in a tangential channel allows to avoid energy losses owing to rotation of a stream in an exit channel.
СРАВНИТЕЛЬНЫЙ АНАЛИЗ РАБОЧИХ ХАРАКТЕРИСТИК СТРУЙНЫХ НАГНЕТАТЕЛЕЙ ВИХРЕВОГО ТИПА
ПОРІВНЯЛЬНИЙ АНАЛІЗ РОБОЧИХ ХАРАКТЕРИСТИК СТРУМИННИХ НАГНІТАЧІВ ВИХРОВОГО ТИПУ
Keywords: vortex ejector; comparative analysis; vortex chamber pump; numerical calculation; energy performance; вихревой эжектор; сравнительный анализ; вихрекамерный насос; численный расчет; энергетические показатели; вихровий ежектор; порівняльний аналіз; вихрекамерний насос; чисельний розрахунок; енергетичні показники; 621.521